Country-by-Country Reporting Goes Public - Cui Bono? - Lagarden, Martin; Schreiber, Ulrich; Simons, Dirk; Sureth-Sloane, Caren (International Transfer Pricing Journal)
After the introduction of CbCR – pursuant to the BEPS Project (Action 13) in 2015 –, which was established to reduce the information asymmetry between MNEs and tax authorities of the countries they operate in, now public CbCR – as suggested by the EU Commission in 2016 – is discussed as a next step. Here, the objective is to overcome information asymmetries between MNEs and the general public of the countries they operate in. Starting from the assumption that regulators care about the legitimacy of tax laws, this article evaluates pros and cons of public CbCR. The authors find that from the perspective of information asymmetries, public CbCR increases tax transparency only marginally at best. Accordingly, it is concluded that democracies that are based on the rule of law seem to rely on pillories in terms of public CbCR to enforce fair tax payments.

Information Design in Coordination Games with Risk Dominant Equilibrium Selection - Ebert, Michael; Kadane, Joseph (Jay) B.; Simons, Dirk; Stecher, Jack Douglas

Analyse der Veränderung der zwischenstaatlichen Gewinnaufteilung bei Einführung einer standardisierten Gewinnverteilungsmethode am Beispiel des Einsatzes von 3D-Druckern - Mair, Christina; Scheffler, Wolfram; Senger, Isabell; Sureth-Sloane, Caren

Violations of Dominance in Decision-Making - Kourouxous, Thomas; Bauer, Thomas (Business Research)
A key premise underlying most of the economic literature is that rational decision-makers will choose dominant strategies over dominated alternatives. However, prior literature in various disciplines including business, psychology, and economics document a series of phenomena associated with violations of the dominance principle in decision-making. In this comprehensive review, we discuss conditions under which people violate the dominance principle in decision-making. When presenting violations of dominance in empirical and experimental studies, we differentiate between absolute, statewise, and stochastic (first- and second-order) violations of dominance. Furthermore, we categorize the literature by the leading causes for dominance violations: framing, reference points, certainty effects, bounded rationality, and emotional responses.

Tax Avoidance - Are Banks Any Different? - Müller, Jens; Gawehn, Vanessa

Investment Timing Effects of Wealth Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren (Journal of Business Economics)
We analyze the impact of wealth taxes on investment timing decisions under uncertainty and irreversibility by employing a real options model of the Dixit/Pindyck type. Considering that wealth taxes have been (re-)introduced or are under discussion in many countries, investors need decision rules for tax systems with wealth taxation. We integrate different valuation methods for wealth tax purposes, distinguish between broadly and narrowly defined wealth taxes and vary the wealth tax rate to ascertain which wealth tax design is more or less likely to accelerate or delay investment. Our main findings are threefold. First, historical cost valuation reduces the distortive timing effects of wealth taxation compared to fair value accounting. Second, broadening the wealth tax base tends to accelerate investment during high interest rate periods and delay investment during low interest rate periods. Our results predict that wealth taxes with a broad tax base are likely to discourage risky investment in times of near-zero interest rates. These distortive wealth tax base effects, however, can be avoided by granting sufficiently high depreciation deductions for wealth tax purposes. Third, the investment timing effects of wealth tax rate variations are very sensitive to the riskiness of the underlying investment. Moreover, investment timing effects crucially depend upon the depreciation rate for wealth tax purposes. A tax legislator who aims to encourage risk taking should introduce generous depreciation deductions. Our study indicates that if a wealth tax is considered to be politically inevitable, possible harmful investment effects can be mitigated by choosing appropriate valuation methods and parameters.

Ein Lösungsvorschlag zur Vermeidung der überschießenden Wirkung der Grunderwerbsteuerreform bei börsennotierten Kapitalgesellschaften - Arbeitskreis Steuern der Schmalenbach-Gesellschaft für Betriebswirtschaft, .; Sureth-Sloane, Caren (Betriebs-Berater)
Der Beitrag stellt die teilweise überschießende Wirkung des Referentenentwurfs des Bundesministeriums der Finanzen zur Grunderwerbsteuer mit Blick auf börsennotierte Kapitalgesellschaften dar und schlägt eine Erweiterung des Referentenentwurfs vor, wobei börsennotierte Kapitalgesellschaften vom Anwendungsbereich der neuen Vorschrift ausgenommen werden sollen.

What are the Drivers of Tax Complexity for MNCs? Global Evidence - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren (Intertax)
All over the world, firms and governments are increasingly concerned about the rise in tax complexity. To manage it and develop effective simplification measures, detailed information on the current drivers of complexity is required. However, research on this topic is scarce. This is surprising as the latest developments-for example, those triggered by the BEPS project-have given rise to the conjecture that complexity drivers may have changed, thus questioning the findings of prior studies. In this article, we shed light on this issue and provide a global picture of the current drivers of tax complexity that multinational corporations face based on a survey of 221 highly experienced tax consultants from 108 countries. Our results show that prior complexity drivers of the tax code are still important, with details and changes of tax regulations being the two most important complexity drivers. We also find evidence for new important complexity drivers emerging from different areas of the tax framework, such as inconsistent decisions among tax officers (tax audits) or retroactively applied tax law amendments (tax enactment). Based on the tax consultants' responses, we develop a concept of tax complexity that is characterized by two pillars, tax code and tax framework complexity and illustrates the various aspects that should be considered when assessing the complexity of a country's tax system.

What are the Drivers of Tax Complexity for MNCs? Global Evidence - Hoppe, Thomas; Sturm, Susann; Sureth-Sloane, Caren (Intertax)

BWL greift gesellschaftlichen Wandel auf - Wolff, Birgitta; Sureth-Sloane, Caren; Weissenberger, Barbara (Frankfurter Allgemeine Zeitung)

Taxation and Agency Conflicts between Firm Owners and Managers: A Review - Bauer, Thomas; Kourouxous, Thomas; Krenn, Peter (Business Research)
When analyzing the influence of taxation on agency conflicts between firm owners and managers, one can draw on theoretical principal–agent literature from various research fields. In recent years, this interdisciplinary research has grown significantly covering research with regards to optimal compensation, investment decisions, tax avoidance and transfer pricing while analyzing the effects of corporate income taxes, wage taxes, bonus taxes and shareholder taxes. Our paper provides a comprehensive review of analytical literature that studies the influence of taxation on agency conflicts between firm owners and managers. Above and beyond summarizing research findings, we discuss how taxes are commonly implemented in agency models, derive empirical predictions, and identify research gaps for future tax research.

Restrukturierungen: operative und finanzielle Wertbeiträge. Eine Betrachtung vor dem Hintergrund der Entwicklungen bei thyssenkrupp - Sievers, Sönke; Sureth-Sloane, Caren; Uhde, André (Die Wirtschaftsprüfung)
Restrukturierungen werden sowohl durch die Digitalisierung, aber auch durch klassische Themen – beispielsweise die Notwendigkeit von Umsatz- und Kostensynergien in kompetitiven Märkten – verstärkt vorangetrieben. Dieser Beitrag beleuchtet vor allem die Motive und Folgen aus wissenschaftlicher Perspektive, indem großzahlige empirische Befunde zu den Themen Beschäftigung, Finanzkennzahlen und Kapitalerhöhungen sowie steuerliche Motive prägnant zusammengefasst und im Kontext des geplanten Joint Ventures von thyssenkrupp und Tata Steel diskutiert werden.

BWL greift gesellschaftlichen Wandel auf - Sureth-Sloane, Caren; Wolff, Birgitta (Frankfurter Allgemeine Zeitung)

Warum ist unser Steuersystem so komplex? Eine befragungsbasierte Analyse - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren (Die Wirtschaftsprüfung)
Die Komplexität des Steuersystems stellt auch in Deutschland ein großes Problem dar. Entgegen bisherigen Betrachtungen weist die vorliegende Befragungsstudie darauf hin, dass die Treiber für steuerliche Komplexität deutlich vielfältiger und nicht nur im Gesetz, sondern auch in den steuerlichen Rahmenbedingungen zu verorten sind. Einerseits tragen übermäßig viele Details und häufige oder umfangreiche Änderungen in erheblichem Maße dazu bei, dass Regelungen – wie solche zu Verrechnungspreisen – als komplex beurteilt werden. Andererseits erweisen sich auch inkonsistente Entscheidungen im Rahmen von Betriebsprüfungen und mangelhafte Gesetzesentwürfe als wesentliche Komplexitätstreiber. Statt einer permanenten Ausweitung von Regulierung sollte künftig der Abbau der im Beitrag identifizierten Probleme gezielt in den Fokus von Wissenschaft, Politik und Praxis rücken.
Keywords: Steuersystem; Komplexität; Steuergesetz; Steuerliche Rahmenbedingungen; BEPS

2016 Global MNC Tax Complexity Survey - Executive Summary - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren

What are the Drivers of Tax Complexity for Multinational Corporations? Evidence from 108 Countries - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren
All over the world, firms and governments are increasingly concerned about the rise in tax complexity. To manage it and develop effective simplification measures, detailed information on the current drivers of complexity is required. However, research on this topic is scarce. This is surprising as the latest developments—for example, triggered by the BEPS project—give rise to the conjecture that complexity drivers may have changed, thus questioning the findings of prior studies. In this paper, we shed light on this issue and provide a global picture of the current drivers of tax complexity that multinational corporations face based on a survey of 221 highly experienced tax practitioners from 108 countries. Our results show that prior complexity drivers of the tax code are still relevant, with details and changes of tax regulations being the two most influential complexity drivers. We also find evidence for new relevant complexity drivers emerging from different areas of the tax framework, such as inconsistent decisions among tax officers (tax audits) or retroactively applied tax law amendments (tax enactment). Based on the responses of the practitioners, we develop a concept of tax complexity that distinguishes two pillars, tax code and tax framework complexity, and illustrates the various aspects that should be considered when assessing the complexity of a country’s tax system.
Keywords: Complexity Drivers; International Comparison; Survey; Tax Complexity; Tax Practitioners

When Do Managers Highlight Their Effective Tax Rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren

Tax Loss Offset Restrictions and Biased Perception of Risky Investments - Mehrmann, Annika; Sureth-Sloane, Caren

Capital Charge Rates, Investment Incentives and Taxation - Bauer, Thomas; Kourouxous, Thomas (European Accounting Review)
This paper studies the impact of personal and corporate income taxation on capital charge rates in a delegation setting with a risk-averse manager. If the investment level influences the riskiness of the investment project, the capital charge rate deviates from the firm's cost of capital and depends crucially on the manager's personal income tax rate. Contradicting conventional wisdom, we find that a higher personal income tax rate induces higher investment expenditures and, surprisingly, increases the capital charge rate. The countervailing effect that a higher capital charge rate induces higher and not lower investment expenditures persists for pre-tax and after-tax performance measures as well as when the tax deductibility of managerial compensation is limited. Corporate income tax causes a similar effect only in the case of limited tax deductibility of compensation. Our insights remain valid regardless of the financing structure and the risk attitude of the investors.

Accounting quality in private firms during the transition towards international standards - Valentincic, Aljosa; Novak, Ales; Kosi, Urska (Accounting in Europe)
We study the historical development of Slovenian Accounting Standards (SAS) and their association with accounting quality (AQ). We focus on private firms where the financial reporting process is characterised by low demand for high-quality reporting. We investigate three distinct editions of SAS since 1994 and test how their development towards international standards is related to AQ. Aggregate earnings management measures indicate that the use of accounting discretion decreases with less earnings smoothing over time. The main features of AQ have been consistent throughout historical development. Asymmetric timeliness of earnings, the ability of earnings to predict future cash flows, and the ability of accruals to mitigate mismatching are all present throughout. We also document typical departures from properties of high AQ. For example, accruals do not (always) facilitate timely recognition of losses. However, these can be attributed to the overwhelming influence of reporting incentives (e.g. taxation, debt, size) rather than to the (lower) quality of accounting standards.  Full Article  Figures & data References  Citations Metrics  Reprints & Permissions  PDF Abstract We study the historical development of Slovenian Accounting Standards (SAS) and their association with accounting quality (AQ). We focus on private firms where the financial reporting process is characterised by low demand for high-quality reporting. We investigate three distinct editions of SAS since 1994 and test how their development towards international standards is related to AQ. Aggregate earnings management measures indicate that the use of accounting discretion decreases with less earnings smoothing over time. The main features of AQ have been consistent throughout historical development. Asymmetric timeliness of earnings, the ability of earnings to predict future cash flows, and the ability of accruals to mitigate mismatching are all present throughout. We also document typical departures from properties of high AQ. For example, accruals do not (always) facilitate timely recognition of losses. However, these can be attributed to the overwhelming influence of reporting incentives (e.g. taxation, debt, size) rather than to the (lower) quality of accounting standards.
Keywords: private firms; accounting quality; development of accounting standards; IFRS-like standards; Slovenia

Boon or Bane? Advance Tax Rulings as a Measure to Mitigate Tax Uncertainty and Foster Investment - Diller, Markus; Kortebusch, Pia; Schneider, Georg; Sureth-Sloane, Caren (European Accounting Review)
Politicians and tax practitioners often claim that tax uncertainty negatively affects investment. In many countries, firms can request fee-based advance tax rulings (ATRs) to mitigate tax uncertainty. We analyse theoretically the circumstances under which investors request ATRs, how tax authorities should price them and how they can affect investment. We assume that tax authorities integrate investors’ reasoning into their decisions. We find that in special cases the optimal fee tax authorities should charge is prohibitively high, thus firms will refrain from requesting ATRs. However, we find that revenue-maximising tax authorities offer ATRs if the ruling enables them either to significantly reduce their tax audit costs or to increase the probability of detecting ambiguous tax issues. Under certain circumstances, ATRs may effectively foster investment and potentially benefit both the tax authorities and taxpayers. Our results provide new explanations for why taxpayers that face high levels of tax uncertainty often do not request ATRs, even when the fee is rather low. Our results also hold when the tax authority maximises social wealth instead of its revenues. Regulatory changes in ATR requirements might serve as a natural quasi-experiment for an empirical study of our predictions regarding investment decisions.

Discretionary aggregation - Ebert, Michael; Simons, Dirk; Stecher, Jack D (The Accounting Review)

Hold or Sell? How Capital Gains Taxation Affects Holding Decisions - Hegemann, Annika; Kunoth, Angela; Rupp, Kristina; Sureth-Sloane, Caren (Review of Managerial Science)
Investments with exit flexibility require decisions regarding both the investment and holding period. Because selling an investment often leads to taxable capital gains, which crucially depend on the duration of an investment, we investigate the impact of capital gains taxation on exit timing under different tax systems. We observed that capital gains taxation delays exit decisions but loses its decision relevance for very long holdings. Often the optimal exit time, which indicates the maximal present value of future cashflows, cannot be determined analytically. However, we identify the breakeven exit time that guarantees present values exceeding those of an immediate sale. While, after-taxes, an immediate sale is often optimal, long holding periods might also be attractive for investors depending on the degree of income and corporate tax integration. A classic corporate tax system often indicates holdings over more than 100 periods. By contrast, a shareholder relief system indicates the earliest breakeven exit time and thus the highest level of exit timing flexibility. Surprisingly, high retention rates are likely to accelerate sales under a classic corporate system. Additionally, the worst exit time, which should be avoided by investors, differs tremendously across tax systems. For an integrated tax system with full imputation, the worst time is reached earlier than under partial or non-integrated systems. These results could help to predict investors’ behavior regarding changes in capital gains taxation and thus are of interest for both investors and tax policymakers. Furthermore, the results emphasize the need to control for the underlying tax system in cross-country empirical studies.

Eigenkapitalverzehr und Substanzbesteuerung deutscher Unternehmen durch eine Vermögensteuer – eine empirische Analyse - Hoppe, Thomas; Maiterth, Ralf; Sureth-Sloane, Caren (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung)
Die (Wieder-)Einführung einer Vermögensteuer ist in den vergangenen Jahren erneut in den Fokus der politischen Diskussion gerückt. Der vorliegende Beitrag vermittelt einen Eindruck von den Belastungswirkungen, die aus der Umsetzung von aktuell vorliegenden Besteuerungskonzepten resultieren würden. Auf der Basis von realen Jahresabschlussdaten wird eine mehrperiodige Veranlagungssimulation durchgeführt, die insbesondere ermöglicht, den zu erwartenden Eigenkapitalverzehr sowie den Anstieg der Steuerbelastung für die betrachtete Stichprobe zu quantifizieren. Von besonderem Interesse sind hierbei Unternehmen, deren laufende Erträge nicht ausreichen, um die Belastungen durch die Vermögensteuer zu tragen und damit einem Substanzverzehr ausgesetzt sind. Es zeigt sich, dass etwa die Hälfte der Unternehmen im Untersuchungszeitraum von sechs Jahren in mindestens einem Jahr einen Substanzverzehr erfährt. Der Vermögensteuer kommt somit keinesfalls der vielfach postulierte Charakter einer eher mäßig belastenden und im Wesentlichen substanzverschonenden Steuer zu. Zusatzbelastungen von knapp 100 bis zu 300 % der Ertragsteuerlast sind keine Seltenheit und veranschaulichen das Gefährdungspotenzial dieser Steuer für den Wirtschaftsstandort Deutschland.
Keywords: Steuerbelastung; Substanzbesteuerung; Ungleiche Vermögensverteilung; Veranlagungssimulation; Vermögensteuer

Tax Loss Offset Restrictions and Biased Perceptions of Risky Investments - Mehrmann, Annika; Sureth-Sloane, Caren

Besteuerung und Rechtsformwahl - König, Rolf; Sureth-Sloane, Caren

Interest Barrier and Capital Structure Response - Alberternst, Stephan; Sureth-Sloane, Caren
The Organisation for Economic Co-Operation and Development (OECD) recently proposed an interest barrier to fight tax base erosion and profit shifting (BEPS). We use the introduction of such an interest deductibility restriction in Germany as a quasi-experiment and find significant corporate capital structure responses. Using single entity financial statements and a detailed matching approach, we find evidence that companies that are affected by the interest barrier reduce their leverage by 4.7 percentage points more than non-affected companies. The effects are stronger among non-financially constrained firms. Our results imply that interest barrier effects on capital structure have so far been heavily underestimated.

Are international accounting standards more credit relevant than domestic standards? - Florou, Annita; Kosi, Urska; Pope, Peter F (Accounting and Business Research)
We examine whether the credit relevance of financial statements, defined as the ability of accounting numbers to explain credit ratings, is higher after firms are required to report under International Financial Reporting Standards (IFRS). We find an improvement in credit relevance for firms in 17 countries after mandatory IFRS reporting is introduced in 2005; this increase is higher than that reported for a matched sample of US firms. The increase in credit relevance is particularly pronounced for higher risk speculative-grade issuers, where accounting information is predicted to be more important; and for IFRS adopters with large first-time reconciliations, where the impact of IFRS is expected to be greater. These tests provide reassurance that the overall enhancement in estimated credit relevance is driven by accounting changes related to IFRS adoption. Our results suggest that credit rating analysts’ views of economic fundamentals are more closely aligned with IFRS numbers, and that analysts anticipate at least some of the effects of the IFRS transition.
Keywords: IFRS; debt markets; credit ratings; credit relevance

Accounting quality in private firms during the transition to international standards - Valentincic, Aljosa; Novak, Ales; Kosi, Urska

Can the CCCTB Alleviate Tax Discrimination against Loss-Making European Multinational Groups? - Ortmann, Regina; Sureth-Sloane, Caren (Journal of Business Economics)

The Effect of Taxes on Corporate Financing Decisions - Evidence from the German Interest Barrier - Alberternst, Stephan; Sureth-Sloane, Caren
The literature suggests that when taking tax effects into account, debt ought to be prefer-able to equity. Thus, with all else being equal, levered firms are expected to show higher firm values.However, there are no uniform predictions of the size of this tax benefit from interest deductibility nor on the effect of changes in interest deductibility. We believe that the German corporate tax re-form in 2008, which introduced an interest barrier, can serve as a promising “quasi-experiment” to investigate the effects from a reform of interest deductibility. A study of this reform on the basis of German financial statement data is of general interest because, first, similar interest barriers have been introduced in several countries and proposed by the OECD to fight BEPS. Second, the major characteristics of the German tax system can be regarded as representative for most European and major Asian countries. Third, single entity financial statements for German companies allows us to capture tax and capital structure details that have not been available in most prior studies. With significance at the 5% level, we find evidence that the companies that are affected by the interest barrier reduce their leverage by 4.7 percentage points more than companies that are not affected by the interest barrier. We are the first to employ a detailed matching approach to the underlying rich dataset, which enables us to overcome several limitations of previous studies. Our results imply that capital structure reactions most likely have been underestimated in previous studies.

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups?, - Ortmann, Regina
Formulary apportionment is an intensively debated mechanism for allocating tax base within multinational groups. Systems under which the formula is identical in all jurisdictions and systems under which jurisdictions can determine the weights on the formula factors individually can be observed. The latter systems produce uncertainty about the overall tax-liable share of the future group tax base. Counter-intuitively, I identify scenarios under which increased uncertainty leads to higher expected future group income. My results provide helpful insights for firms and policy makers debating the specific design of a formulary apportionment system.

Entscheidungskalküle US-amerikanischer Unternehmen bei Tax Inversions. What Drives the Decision of U.S. Firms to Expatriate? - Oßwald, Benjamin; Sureth-Sloane, Caren (Steuer und Wirtschaft International)

Investment Effects of Wealth Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren

Mehr Theorie wagen: Eine neue Ausbildung für die Praxis? - Sureth, Caren (WiSt - Wirtschaftswissenschaftliches Studium)

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska (Review of Accounting Studies)
We examine whether the mandated introduction of International Financial Reporting Standards (IFRS) is associated with the propensity to access the public rather than private debt market and the cost of debt. We use a global sample of public bonds and private loans and find that mandatory IFRS adopters are more likely, post-IFRS, to issue bonds than to borrow privately. We also find that mandatory IFRS adopters pay lower bond yield spreads, but not lower loan spreads, after the mandate. These findings are consistent with debt providers responding positively to financial reporting of higher quality and comparability, but only when there is a greater reliance on publicly available financial statements than private communication. Lastly, we document that the observed debt market benefits are concentrated in countries with larger differences between domestic GAAP and IFRS and are present even for EU countries that did not experience concurrent financial reporting enforcement or other institutional reforms. Overall, our study documents positive economic consequences around the mandated IFRS adoption for corporate debt financing and, in particular, for bond financing.
Keywords: Accounting regulation; IFRS; Accounting quality; Public and private debt markets; Cost of debt

Vermögensteuer und ihre Implikationen für den Wirtschaftsstandort Deutschland - eine betriebswirtschaftliche Analyse - Hoppe, Thomas; Maiterth, Ralf; Sureth-Sloane, Caren
Die (Wieder-)Einführung einer Vermögensteuer ist in den vergangenen Jahren erneut in den Fokus der politischen Diskussion gerückt. Der vorliegende Beitrag vermittelt einen Eindruck von den Belastungswirkungen, die aus der Umsetzung von aktuell vorliegenden Besteuerungskonzepten resultieren würden. Auf der Basis von realen Jahresabschlussdaten wird eine mehrperiodige Veranlagungssimulation durchgeführt, die insbesondere ermöglicht, den zu erwartenden Eigenkapitalverzehr sowie den Anstieg der Steuerbelastung für die betrachtete Unternehmensgruppe zu quantifizieren. Von besonderem Interesse sind hierbei Unternehmen deren laufende Erträge nicht ausreichen, um die Belastungen durch die Vermögensteuer zu tragen und damit einem Substanzverzehr ausgesetzt sind. Es zeigt sich, dass etwa die Hälfte der Unternehmen im Untersuchungszeitraum von sechs Jahren in mindestens einem Jahr einen Substanzverzehr erfährt. Der Vermögensteuer kommt somit keinesfalls der vielfach postulierte Charakter einer eher mäßig belastenden und im Wesentlichen substanzverschonenden Steuer zu. Zusatzbelastungen von knapp 100 bis zu 300% der Ertragsteuerlast sind keine Seltenheit und veranschaulichen das Gefährdungspotenzial dieser Steuer für den Wirtschaftsstandort Deutschland.
Keywords: Steuerbelastung; Substanzbesteuerung; ungleiche Vermögensverteilung; Veranlagungssimulation; Vermögensteuer

Editorial: What Is and What Is Not a Substantial Contribution? - Albers, Sönke; Sureth-Sloane, Caren (Business Research)

Can the CCCTB Alleviate Tax Discrimination against Loss-Making European Multinational Groups? - Ortmann, Regina; Sureth-Sloane, Caren

Can Tax Rate Increases Foster Investment Under Entry and Exit Flexibility? - Insights from an Economic Experiment - Fahr, Rene; Janssen, Elmar A.; Sureth-Sloane, Caren

Do Investors Request Advance Tax Rulings to Alleviate Tax Risk (and do tax authorities provide them)? A Joint Taxpayers’ and Tax Authorities’ View on Investment Behavior - Diller, Markus; Kortebusch, Pia; Schneider, Georg; Sureth-Sloane, Caren

Thin Capitalization Rules and Entrepreneurial Capital Structure Decisions - Maßbaum, Alexandra; Sureth-Sloane, Caren (Business Research)

IFRS 7 Disclosures and Risk Perception of Financial Instruments - Bischof, Jannis; Ebert, Michael (Schmalenbach Business Review)

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska

Cost of Debt for Private Firms Revisited: Voluntary Audits as a Reflection of Risk - Koren, Jernej; Kosi, Urska; Valentincic, Aljosa

Determinants of corporate participation in the IFRS 4 (insurance contracts) replacement process - Kosi, Urska; Reither, Antonia (Accounting in Europe)
This study examines the determinants of financial firms' lobbying behaviour in the replacement process of International Financial Reporting Standard 4 (IFRS 4) Insurance Contracts. Based on comment letters in response to International Accounting Standards Board's (IASB) Exposure Draft 2010/8, we investigate firms' lobbying decisions and their long-term lobbying intensity. Using an international sample of publicly listed financial firms, we show that insurance companies and financially constrained IFRS firms are more likely to lobby the IASB. We also examine the long-term lobbying activity in the IFRS 4 replacement process during the years 2007–2010. We find that insurance companies and firms with dispersed ownership lobby more. Our results are stronger for IFRS firms compared to US generally accepted accounting principles users. Overall, we document intense lobbying by financial firms and present results that are largely consistent with economic consequences of anticipated accounting changes being the main driver of firms' lobbying behaviour. These results are in line with prior findings for non-financial firms.
Keywords: standard setting; IASB; corporate lobbying; financial firms; IFRS 4

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Koren, Jernej; Kosi, Urska; Valentincic, Aljosa (SSRN Electronic Journal)
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.

Besteuerung und Rechtsformwahl - König, Rolf; Sureth-Sloane, Caren

Der Einfluss von Steuern auf Investitionsentscheidungen bei Unsicherheit - Sureth, Caren

Does Financial Statement Audit Reduce the Cost of Debt of Private Firms? - Kosi, Urska; Koren, Jerney; Valentincic, Aljosa
This study examines the effect of audit on private firms’ cost of debt. We use a sample of 1,949 small private firms operating in the period 2006-2010 with optional financial statement audit. High quality data allows us to construct a more precise interest rate measure than existing studies employ. After controlling for obvious sources of demand for voluntary audits (ownership complexity, subsidiary status, bank relations), we find a robust central result that voluntary audits increase rather than decrease the cost of debt financing, contrary to several existing studies. This finding indicates that voluntary audits are generally treated as “adopting a label” and penalised by creditors, regardless of the perceived auditor quality as a result of the lemon problem in the audit market. Even Big-4 audits increase the cost of debt, likely as a result due to the lemon problem in the audit market, although the increase is smaller than for non-Big-4 audits. The results are sensitive to the estimation method used (OLS, Heckman’s two-step, PSM) and (sub-)sample selection. We show that disregarding the underlying assumptions of these estimation methods may lead to incorrect inferences. Additional analyses show that audited firms’ reported earnings are less informative about future operating performance than earnings of their unaudited counterparts. Our results also indicate that results are sensitive to cost of debt definition and this might have affected the results reported in the existing literature.
Keywords: private firms; voluntary audit; cost of debt; self-selection bias; lemon problem

Does Mandatory IFRS Adoption Improve the Credit Relevance of Accounting Information? - Kosi, Urska; Florou, Annita; Pope, Peter F.

Write-offs and profitability in private firms: Disentangling the impact of tax-minimisation incentives - Kosi, Urska; Valentincic, Aljosa (European Accounting Review)
Private firms are likely to use the financial reporting process more for other objectives, such as tax savings, than for communicating performance. However, observing firms choosing accounting policies for tax-minimisation purposes is not straightforward due to (i) tax and non-tax costs of reporting lower income (ii) accounting policies that result in lower reported income and no tax savings but generate non-tax benefits (iii) preparers' multiple incentives and (iv) econometric issues. We observe a large sample of 20,505 private firms writing off assets in two separate regimes, one that generates tax savings and one that does not. Firms significantly decrease, but continue to use, write-offs after the adverse change in tax treatment of write-offs. The exogenous tax change should not affect other reporting incentives. This allows us to disentangle the tax-minimisation incentive from other (un-observable) incentives, including debt contracting, dividends and employee relations that contribute to the observed anomalous positive relationship between write-offs and profitability. We show that for private firms (i) obtaining tax savings is important overall (ii) non-tax costs and benefits are probably also important and (iii) earnings informativeness for future cash flows increases after the adverse tax legislation change.

Does mandatory IFRS adoption facilitate debt financing? - Florou, Annita; Kosi, Urska

Sooner or Later? – Paradoxical Investment Effects of Capital Gains Taxation under Simultaneous Investment and Abandonment Flexibility - Niemann, Rainer; Sureth-Sloane, Caren (European Accounting Review)

Advance Pricing Agreements (APAs) als Instrument zur Vermeidung von Verrechnungspreiskonflikten – eine kritische Betrachtung - Vollert, Pia; Eikel, Carolin; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Mehr Theorie wagen. Betriebswirtschaftslehre nach Bologna oder Hochschulbildung im Wandel - Sloane, Peter F. E.; Sureth-Sloane, Caren (Wirtschaft und Beruf)

Unternehmensführung und interkulturelle Hochschulbildung. Unternehmensführung in Europa - Interkulturelle Fragen - Sureth-Sloane, Caren (Wirtschaft und Beruf)

Wertorientierte Vergütung des Aufsichtsrats - Auswirkungen auf den Unternehmenswert - Ebert, Michael; Zein, Nicole (Betriebswirtschaftliche Forschung und Praxis)

Der Einfluss der Zinsschranke auf unternehmerische Kapitalstrukturentscheidungen - Maßbaum, Alexandra; Klotzkowski, Tasja; Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)

Does insider shareholding matter to corporate payout reactions to tax reforms? - Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)

Die Einkommensbesteuerung von international tätigen Künstlern, Sportlern, Artisten und unterhaltend Darbietenden - Führt die Neuregelung zu einer gleichmäßigen Besteuerung? - Dahle, Claudia; Sureth-Sloane, Caren; Stamm, Katharina (Steuern und Bilanzen)

ProDok Helps to Transform Doctoral Training at Business Schools in German-Speaking Countries - Jahnke, Hermann; Sureth-Sloane, Caren (POMS Chronicle)

The Mixed Accounting Model Under IAS 39: Current Impact on Bank Balance Sheets and Future Developments - Ebert, Michael; Bischof, Jannis (The Capco Institute Journal of Financial Transformation)

The Impact of Differential Capital Income Taxation on the Value of Risky Projects - Niemann, Rainer; Sureth-Sloane, Caren (Economics Bulletin)

§§ 20 bis 23 UmwStG: Die Einbringung von Unternehmensteilen in eine Kapitalgesellschaft - Ansatz von Buchwerten oder gemeinen Werten - Maßbaum, Alexandra; Sureth-Sloane, Caren (Steuer und Studium)

Handels- und steuerrechtliche Kapitalkontenfortschreibung und deren Einfluss auf die Verlustverrechnung bei Personengesellschaften - Kopplin, Anja; Maßbaum, Alexandra; Sureth-Sloane, Caren (Die Wirtschaftsprüfung)

Empirische Analyse der Unternehmensbewertung für die Erbschaftsteuer mit dem vereinfachten Ertragswertverfahren - Müller, Jens; Sureth-Sloane, Caren

Mögliche Fallstricke einer Optimierung unternehmerischer Investitionsentscheidungen auf der Grundlage der Konzernsteuerquote - Müller, Jens; Sureth-Sloane, Caren; Läufer, Christian (Die Wirtschaftsprüfung)

Wichtigste Einflussfaktoren auf die steuerliche Verlustnutzung bei Personengesellschaften - Sureth-Sloane, Caren (Steuer und Studium)

Besteuerung multinationaler Unternehmen in der EU – eine vergleichende Analyse ausgewählter Reformvorschläge - Sureth-Sloane, Caren; Bäumer, Michaela (Zeitschrift für Betriebswirtschaft)

Capitalized investments with entry and exit options and paradoxical tax effects - Schneider, Georg; Sureth-Sloane, Caren (Review of Managerial Science)

Wie attraktiv sind Beteiligungsinvestitionen nach der Begrenzung der Verlustnutzung bei Anteilskäufen durch § 8c KStG? - Sureth-Sloane, Caren; Vollert, Pia (Corporate Finance biz)

The Impact of Tax Optimized Investment Projects on the Effective Group Tax Rate - Müller, Jens; Sureth-Sloane, Caren (Die Betriebswirtschaft)

Grenzüberschreitende Verlustverrechnungssysteme in Europa – Vorbilder für eine Reform der deutschen Organschaft? - Sureth-Sloane, Caren; Mehrmann, Annika; Dahle, Claudia (Steuer und Wirtschaft)

Mikroanalytische Begleitung der Steuerpolitik am Beispiel der Erbschaftsteuerreform - Maiterth, Ralf; Houben, Henriette; Broekelschen, Wiebke; Müller, Jens; Sureth-Sloane, Caren (Statistik und Wissenschaft)
Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation | Deutschland | Germany
Keywords: Erbschaftsteuer | Inheritance tax | Steuerreform | Tax reform | Steuerwirkung | Tax effects | Steuereinnahmen | Tax revenue | Mikrodaten | Microdata | Simulation

Bilanzpolitisches Potential im Rahmen der Goodwillbilanzierung - Transaktionsgestaltung beim Unternehmenserwerb - Ebert, Michael; Simons, Dirk (KoR : Zeitschrift für internationale und kapitalmarktorientierte Rechnungslegung)

International corporate reporting: A comparative approach, by Clare Roberts, Pauline Weetman and Paul Gordon (fourth edition) - Kosi, Urska (The International Journal of Accounting)

Versinkt die Kapitalmarkttheorie in logischen Widersprüchen, oder: Ist arqus e.V. aus dem Schneider? - Blaufus, Kay; Hundsdoerfer, Jochen; Kiesewetter, Dirk; König, Rolf J.; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Niemann, Rainer; Schanz, Deborah; Sureth-Sloane, Caren; Treisch, Corinna (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung)

arqus-Stellungnahme zur notwendigen Reform der Abgeltungssteuer - Kiesewetter, Dirk; Niemann, Rainer; Hundsdoerfer, Jochen; Knirsch, Deborah; König, Rolf; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Sureth-Sloane, Caren; Treisch, Corinna (Der Betrieb)

arqus-Stellungnahme: Das BilMoG - Eine Chance zur Steuervereinfachung? - Knirsch, Deborah; Müller, Heiko; Blaufus, Kay; Hundsdoerfer, Jochen; Kiesewetter, Dirk; König, Rolf; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Sureth-Sloane, Caren; Treisch, Corinna (Deutsches Steuerrecht)

Steuern und Risiko als substitutionale oder komplementäre Determinanten unternehmerischer Investitionspolitik? - Niemann, Rainer; Sureth-Sloane, Caren

Auswirkungen einer Reform des Erbschaft- und Schenkungsteuergesetzes auf das Steueraufkommen unter besonderer Berücksichtigung einer verkehrswertorientierten Bewertung von Unternehmens- und Grundvermögen - Sureth-Sloane, Caren; Müller, Jens; Houben, Henriette; Maiterth, Ralf (Untrnehmensbesteuerung 2008: Neue Wege gehen)

Asset Write-Offs in the Absence of Agency Problems - Garrod, Neil; Kosi, Urska; Valentincic, Aljosa (Journal of Business Finance and Accounting)
Using a large sample of small private companies, we show incremental influence ofeconomic incentives over prescriptions from accounting standards by financial statementpreparers in a code‐law setting with high alignment between financial and tax reportingand no agency problems. Contrary to predictions from standards, more profitable companiesare more likely to write‐off and the write‐off magnitude is greater, reflecting taxminimisation. Larger companies are more likely to write‐off, but the magnitude decreaseswith size, reflecting increasing political costs due to greater visibility to taxauthorities. Previous write‐off patterns and magnitudes are persistent, reflectinginstitutional learning linked to regulatory changes.

The impact of minimum taxation by an imputable wealth tax on capital budgeting and business strategy of German companies - Sureth-Sloane, Caren; Maiterth, Ralf (Review of Managerial Science)

Steuern und Risikobereitschaft in Modellen irreversibler Investitionen - Niemann, Rainer; Sureth-Sloane, Caren (Journal für Betriebswirtschaft)

arqus-Stellungnahme: Das BilMoG - Eine Chance zur Steuervereinfachung? - Müller, Heiko; Blaufus, Kay; Hundsdoerfer, Jochen; Kiesewetter, Dirk; König, Rolf; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Niemann, Rainer; Sureth-Sloane, Caren; Treisch, Corinna (Deutsches Steuerrecht)

arqus-Stellungnahme zur faktischen Abschaffung der Erbschaftsteuer für Unternehmer - Maiterth, Ralf; Niemann, Rainer; Blaufus, Kay; Kiesewetter, Dirk; Knirsch, Deborah; König, Rolf; Hundsdoerfer, Jochen; Müller, Heiko; Sureth-Sloane, Caren; Treisch, Corinna (Der Betrieb)

Unternehmensfinanzierung, Unternehmensrechtsform und Besteuerung - Maiterth, Ralf; Sureth-Sloane, Caren

Steuerreformen und Übergangsprobleme bei Beteiligungsinvestitionen - Sureth-Sloane, Caren

Advances in performance measurement: evidence from Slovenian companies - Tekavic, Metka; Peljhan, Darja; Kosi, Urska (Accounting and Finance in Transition)

Advances in Performance Measurement: Evidence from Slovenian Companies - Peljhan, Darja; Tekavcic, Metka; Kosi, Urska (Accounting and Finance in Transition)
Performance measurement systems are the focus of considerable attention in academic and practitioner communities as they contribute to the management of organisational performance. The literature suggests that companies have to put much more emphasis on non-financial measures than they did in the past and that they should implement some kind of integrated performance measurement system. The purpose of our exploratory study was to find out characteristics of performance measurement and management in Slovenian companies. We conducted a survey ‘Performance management in Slovenian companies’ in the spring of 2003. Our sample consists of 108 Slovenian companies. The research results show that Slovenian companies still perceive financial performance measures as more important than non-financial, although they measure both perspectives of their business. Also, we found out that companies measure their performance unsystematically as only 54 per cent of companies that have not changed their performance measurement methods in the last five years use balanced scorecard or some other form of integrated performance measurement system.

Unternehmensfinanzierung, Unternehmensrechtsform und Besteuerung - Maiterth, Ralf; Sureth-Sloane, Caren (Betriebswirtschaftliche Forschung und Praxis)

Verbessern Tax-Master- und WP-Master-Studiengänge die Ausbildungsqualität von Steuerberatern und Wirtschaftsprüfern? - Bareis, Peter; Hachmeister, Dirk; Kahle, Holger; Kiesewetter, Dirk; König, Rolf; Maiterth, Ralf; Niemann, Rainer; Rückle, Dieter; Schneider, Dieter; Siegel, Theodor; Sureth-Sloane, Caren; Treisch, Corinna (Zeitschrift für Steuern und Recht)

Auswirkungen der Vermögensteuer als Mindeststeuer auf die Investitionstätigkeit und die Attraktivität Deutschlands im internationalen Standortwettbewerb - Maiterth, Ralf; Sureth-Sloane, Caren (Steuern und Bilanzen)

Wiedereinführung der Vermögensteuer als Mindeststeuer in Deutschland - Unlösbare Probleme bei der Bewertung von Grundbesitz und Unternehmen - Maiterth, Ralf; Sureth-Sloane, Caren (Steuern und Bilanzen)

Wealth Tax As Alternative Minimum Tax? - The Impact of a Wealth Tax on Business Structure and Strategy - Sureth-Sloane, Caren; Maiterth, Ralf

Capital Budgeting with Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren (Journal of Economics and Statistics)

Aktuelle Änderungen beim Betriebsausgabenabzug - Geschenke, Bewirtungskosten, Fahrtkostenzuschüsse und Halbjahres-AfA - Sureth-Sloane, Caren; Müller, Jens; Nordhoff, Daniel (BBK - Buchführung, Bilanzierung, Kostenrechnung)

Modelle für die Vermögensbesteuerung von natürlichen Personen und Kapitalgesellschaften - Konzepte, Aufkommen, wirtschaftliche Wirkungen - Bach, Stefan; Haan, Peter; Maiterth, Ralf; Sureth-Sloane, Caren (DIW Berlin: Politikberatung kompakt)

Tax neutrality under irreversibility and risk aversion - Niemann, Rainer; Sureth-Sloane, Caren (Economics Letters)